2014
DOI: 10.1002/eco.1523
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal water use by deciduous and evergreen woody species in a scrub community is based on water availability and root distribution

Abstract: In a seasonally dry plant community of central Florida, USA, that experiences water limitation in the dry season and high water availability in the wet season, we first tested whether evergreen woody species shift from shallow water in the wet season to deep water in the dry season. Second, we tested whether deciduous woody species restrict water uptake to the shallow soil during the wet season and cease water uptake during the dry season. To address these questions, we measured water source use of two deciduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 64 publications
4
72
1
Order By: Relevance
“…However, several isotope studies have shown that the root water uptake profile does not coincide with the root distribution if plants experience water stress (e.g. Kulmatiski and Beard, 2013;Ellsworth and Sternberg, 2015;Volkmann et al, 2016). Hydraulic lift can further increase the complexity of soil-plant interaction, as experimentally observed and implemented in a soil hydraulic model by Meunier et al (2018).…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…However, several isotope studies have shown that the root water uptake profile does not coincide with the root distribution if plants experience water stress (e.g. Kulmatiski and Beard, 2013;Ellsworth and Sternberg, 2015;Volkmann et al, 2016). Hydraulic lift can further increase the complexity of soil-plant interaction, as experimentally observed and implemented in a soil hydraulic model by Meunier et al (2018).…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Thus, the assumption of a linear decrease in root water uptake with depth appears to be reasonable for the current study sites. However, several isotope studies have shown that, the root water uptake profile does not coincide with the root distribution if plants experience water stress (e.g., Kulmatiski and Beard, 2013;Ellsworth and Sternberg, 2015;Volkmann et al, 2016). Hydraulic lift 5 can further increase the complexity of soil-plant interaction, as experimentally observed and implemented in a soil hydraulic model by Meunier et al (2018).…”
Section: Limitations and Outlookmentioning
confidence: 99%
“…This fundamental understanding of water uptake and transport from roots to shoots underlies the utility of stable isotopes in plant water uptake investigations17. While many site-based studies have now been completed18192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114…”
mentioning
confidence: 99%